Effect of Mirror Therapy on Complex Regional Pain Syndrome Post Wrist Burn in Children with Type I Diabetes: A Randomized Controlled Trial - Farag, Mina Nashat Halim; Younan, Wagdy William Amin; Ghattas, 3Emad Makram; Mahfouz Mahmoud, Marwa Mahmoud (International Journal of Psychosocial Rehabilitation, 2020)
Background: Studying of mirror therapy training in complex regional pain syndrome on type I diabetic children is a strategy for determining its efficacy in reducing degree of pain and increase in hand grip and pinch strengthObjective: To evaluate the effectiveness of mirror therapy on complex regional pain syndrome (CRPS) post wrist burn in children with type I diabetes and prevent worsening of the case by neurological complication for diabetesMethods: Thirty diabetic children with CRPS post wrist burn with age ranged from 10 to16 from both genders participated in this study. Children divided randomly into two groups (A &B) of equal number, fifteen children each. All individuals assessed in our study using VAS to assess the degree of pain and using baseline handheld dynamometer to assess hand grip and pinch before starting the treatment protocol and 4 weeks after starting the treatment program.The treatment protocol used for the two groups include: children in study Group (A) received conventional hand progressive exercise program (active, and active resisted hand exercises) for 15 min in addition, the same exercises were done by the sound hand in front of mirror for 15 min. Group (B) received only conventional hand progressive exercise program for 30 min. Both groups participated in 12 sessions and the overall times assigned in both groups are the sameResults: This study revealed statistically significant differences in decrease degree of pain and increase in hand grip and pinch strength, in mirror group than control group. (P value < 0.01)Conclusion: From the finding of this study we concluded that mirror therapy exercise program is an effective, safe, relatively inexpensive, simple, and available modality in decreasing pain and improving function level.